Hi

I would say

\cos \theta \:dr - r\:\sin \theta\:d\theta)" alt="\sin \theta \:dr + r\:\cos \theta\:d\theta = \frac{r\:\sin \theta+r^2\:\cos \theta}{r\:\cos \theta-r^2\:\sin \theta} \\cos \theta \:dr - r\:\sin \theta\:d\theta)" />

\sin \theta \:dr + r\:\cos \theta\:d\theta) = (r\:\sin \theta+r^2\:\cos \theta) \\cos \theta \:dr - r\:\sin \theta\:d\theta)" alt="(r\:\cos \theta-r^2\:\sin \theta)\\sin \theta \:dr + r\:\cos \theta\:d\theta) = (r\:\sin \theta+r^2\:\cos \theta) \\cos \theta \:dr - r\:\sin \theta\:d\theta)" />

Seems strange but ... why not ?